How God becomes real : kindling the presence of invisible others - Luhrmann, T. M. (Tanya M.), 1959- (Princeton University Press, 2020)
"How do gods and spirits come to feel vividly real to people-as if they were standing right next to them? Humans tend to see supernatural agents everywhere, as the cognitive science of religion has shown. But it isn't easy to maintain a sense that there are invisible spirits who care about you. In How God Becomes Real, acclaimed anthropologist and scholar of religion T.M. Luhrmann argues that people must work incredibly hard to make gods real and that this effort-by changing the people who do it and giving them the benefits they seek from invisible others-helps to explain the enduring power of faith"--